Noradrenergic Activation of Hypoglossal Nucleus Modulates the Central Regulation of Genioglossus in Chronic Intermittent Hypoxic Rats - Nie, Xinshi; Zhou, Ling; Wang, Aidi; Jin, Hongyu; Qin, Zheng; Pang, Jian; Wang, Wei; Kang, Jian (Frontiers in Neurology, 2017)
Neuromuscular compensation of the genioglossus muscle can be induced by chronic intermittent hypoxia (CIH) in obstructive sleep apnea to maintain upper airway stability. Noradrenergic activation of hypoglossal nucleus plays a critical role in the central control of the genioglossus. However, it remains unknown whether norepinephrine (NE) takes part in the central regulation of the genioglossus during CIH. Adult male Wister rats (n = 32) were studied to explore the influence of noradrenergic activation of hypoglossal nucleus on the central control of the genioglossus at different stages of CIH. The rats were divided into four groups; normal control or normoxic (NO) group, CIH group, CIH + normal saline (NS) group, and CIH + prazosin (PZ, α1-adrenergic antagonist) group. Prasozin (0.2 mM, 60 nl) and NS (0.9%, 60 nl) were microinjected into the hypoglossal nucleus. The responses of the genioglossus corticomotor area to transcranial magnetic stimulation (TMS) were recorded on the 1st, 7th, 14th, and 21st day of CIH. The CIH group showed significantly shorter TMS latencies on days 1, 7, and 14 (3.85 ± 0.37 ms vs. 4.58 ± 0.42 ms, 3.93 ± 0.17 ms vs. 4.49 ± 0.55 ms, 3.79 ± 0.38 ms vs. 4.39 ± 0.30 ms, P < 0.05), and higher TMS amplitudes on day 1 (2.74 ± 0.87 mV vs. 1.60 ± 0.52 mV, P < 0.05) of CIH than the NO group. Compared to the CIH + NS group, the CIH + PZ group showed decreased TMS responses (longer latencies and lower amplitudes) only on the 14th day of CIH (3.99 ± 0.28 ms vs. 4.61±0.48 ms, 2.51 ± 0.67 mV vs. 1.18 ± 0.62 mV, P < 0.05). These results indicated that noradrenergic activation of the hypoglossal nucleus played a role in the central compensation of genioglossus through α1-adrenoceptor on the 14th day of CIH.